2016
DOI: 10.1097/mop.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

ABO-incompatible heart transplantation

Abstract: Purpose ABO-incompatible (ABOi) heart transplantation (HTx) in young children has evolved from an experimental approach to a standard allocation option in many countries. Clinical and immunological research in ABOi transplantation has revealed insight into the immature immune system and its role in superior graft acceptance in childhood and antigen-specific tolerance. Recent Findings Multicenter experience has confirmed equal actuarial survival, freedom from rejection and graft vasculopathy comparing ABOi to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
0
35
1
Order By: Relevance
“…5 Overall, there was more frequent use of induction therapy in patients having a higher risk of mortality within the first year post-transplant. Surprisingly, although infants have been recognized as generally having a decreased incidence of rejection and a more forgiving immune system, 9 in our cohort these patients were more likely to have received ALA. This may reflect the preferred use of this drug in patients with CHD based on presumed higher risk of early immunologic complications and secondary organ failure.…”
Section: Discussioncontrasting
confidence: 59%
“…5 Overall, there was more frequent use of induction therapy in patients having a higher risk of mortality within the first year post-transplant. Surprisingly, although infants have been recognized as generally having a decreased incidence of rejection and a more forgiving immune system, 9 in our cohort these patients were more likely to have received ALA. This may reflect the preferred use of this drug in patients with CHD based on presumed higher risk of early immunologic complications and secondary organ failure.…”
Section: Discussioncontrasting
confidence: 59%
“…ABO compatibility was defined as an O blood type for mothers and either A or B blood type for children [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Natural anti-A and anti-B antibodies are produced as a presumed immunologic cross-reaction to similar epitopes found on the gut flora. 7 The first protocol for intentional ABOi heart transplantation was developed 20 years ago by West’s group, 7 , 8 with the rationale that the ontogeny of natural isohemagglutinins begins after 4 to 6 months of age, providing a window of opportunity to transplant infants across the ABO barrier safely in the absence of preformed anti-A and anti-B antibodies. 9 Since then, multiple teams worldwide have confirmed that ABOi heart transplantation is a safe procedure in infants and young patients with absent or low circulating isohemagglutinins, saving thousands of lives in the last 2 decades by increasing the donor pool.…”
Section: Nabs and Autoantibodiesmentioning
confidence: 99%